Geochemical characteristics of the extensive peralkaline pyroclastic flow deposit of NW Mexico based on conventional and handheld X-ray fluorescence. Geochemical and tectonic implications in a regional context. - Vidal-Solano, J.R.; Lozano Santa Cruz, R.; Zamora, O.; Mendoza-Cordova, A.; Stock, J.M. (Journal of Iberian Geology, 2013)
Chemical analyses conducted on the surface of rock slabs under a combination of two X-ray spectrometry methods, wavelength dispersive XRF and energy dispersive XRF, are used to establish a geochemical correlation between the studied samples. This proves to be an excellent method for the characterization of volcanic glasses, particularly when particles of exotic origin are present, because the effect of these is not easily eliminated by conventional whole rock analysis. Analyses of glassy rhyolites (ignimbrites and lava flows) in northwestern Mexico establish a geochemical signature for the samples, providing criteria that allow us to: a) correlate them with a peralkaline volcanic event, previously reported, that occurred during Middle Miocene time; b) distinguish them from other metaluminous varieties in the region and, c) propose a correlation between all the peralkaline vitrophyres that crop out within the studied area, of at least 50.000 km2, validating the hypothesis that they are related to the same volcanic event. Finally, based on the results of this study and previous geological investigations, it is proposed that a distance of more than 100 km between the geographical location of the thickest peralkaline deposits in Sonora, is probably related to a displacement along transtensional dextral faults during the Late Miocene.